1988
DOI: 10.1212/wnl.38.6.837
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic infarcts

Abstract: We studied forty patients with CT-proven thalamic infarcts without involvement of the superficial territory of the posterior cerebral artery. The delineation into four arterial thalamic territories (inferolateral, tuberothalamic, posterior choroidal, paramedian) corresponded clinically to four different syndromes. The most common etiologies were lacunar infarction, large artery atherosclerosis with presumed artery-to-artery embolism, cardioembolism, and migrainous stroke. We found no risk factor other than age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
325
4
15

Year Published

1990
1990
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 622 publications
(370 citation statements)
references
References 0 publications
26
325
4
15
Order By: Relevance
“…In our case, decreased consciousness was the result of infarctions in both paramedian thalami and the left rostral midbrain, which then made us suspect an occlusion of the AOP, since vertebrobasilar and posterior circulations were unaffected. Like previous studies [3,4,[6][7][8][9][10][11][12][13], our case showed severe cognitive dysfunctions, especially in attention and verbal long-term memory. Symptoms rapidly improved during early rehabilitation periods.…”
Section: Discussionsupporting
confidence: 87%
“…In our case, decreased consciousness was the result of infarctions in both paramedian thalami and the left rostral midbrain, which then made us suspect an occlusion of the AOP, since vertebrobasilar and posterior circulations were unaffected. Like previous studies [3,4,[6][7][8][9][10][11][12][13], our case showed severe cognitive dysfunctions, especially in attention and verbal long-term memory. Symptoms rapidly improved during early rehabilitation periods.…”
Section: Discussionsupporting
confidence: 87%
“…We speculate that this may have been caused by a transient dysfunction of the bilateral thalami, given the striking signal alteration in this region on MRI. Dysfunction of the right thalamus can cause visuospatial hemineglect on the left side (Bogousslavsky, Regli, & Uske, 1988;De Witte et al, 2011;Watson & Heilman, 1979), and dysfunction of the left thalamus can cause aphasia (Bogousslavsky et al, 1988;De Witte et al, 2011;Kumar, Masih, & Pardo, 1996). For example, in the literature a case has been described where a patient with deep cerebral venous thrombosis with bithalamic infarction presented with a transient left-side visuospatial neglect, aphasia and amnesia (Benabdeljlil et al, 2001), which resembles our case.…”
Section: Discussionsupporting
confidence: 66%
“…CPSP occurs most often after strokes that involve the thalamus [4][5][6][7][8][9]. The quality of life of patients with CPSP is very poor due to daily paroxysms of persistent spontaneous pain and hypersensitivity to noxious (hyperalgesia and allodynia) and non-noxious stimuli (paresthesia and dysesthesia) [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%